2011
DOI: 10.1080/15287394.2011.586940
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Inflammatory and Fibrotic Responses in Fischer 344 Rats After Intratracheal Instillation Exposure to Libby Amphibole

Abstract: Increased incidences of asbestosis have been reported in workers from Libby, MT, associated with exposures to amphibole-contaminated vermiculite. In this study pulmonary and histopathological changes were investigated following Libby amphibole (LA) exposure in a rat model. Rat respirable fractions of LA and amosite (aerodynamic diameter <2.5 μm) were prepared by water elutriation. Male F344 rats were exposed to single doses of either saline (SAL), amosite (0.65 mg/rat), or LA (0.65 or 6.5 mg/rat) by intratrach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 39 publications
3
11
0
Order By: Relevance
“…The importance of fiber length as a determinant for inducing a pro-inflammatory response in HAEC is in accordance with our previous report on the size-fractionated PM 2.5 samples of LA2000 and RTI amosite (LA 2.5 and AM 2.5 , respectively), which were equally pure amphibole samples and demonstrated comparable total surface area values; however the AM 2.5 sample possessed considerably longer fibers as opposed to the LA 2.5 sample and induced a 3-fold greater IL-8 transcriptional response [17]. This hierarchy of potency between the RTI amosite and LA samples observed on an equal mass basis was also consistent with the findings of the animal toxicology studies reported as part of the Libby Action Plan in which rats were dosed by single intratracheal instillation [31]. The concept of particle length as a critical determinant for asbestos toxicity is of course hardly a novel concept as numerous reports have shown correlations between fiber length and carcinogenic outcomes [28,36] as well as on lung injury and inflammation through incomplete phagocytosis of elongated fibers by alveolar macrophages [37].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The importance of fiber length as a determinant for inducing a pro-inflammatory response in HAEC is in accordance with our previous report on the size-fractionated PM 2.5 samples of LA2000 and RTI amosite (LA 2.5 and AM 2.5 , respectively), which were equally pure amphibole samples and demonstrated comparable total surface area values; however the AM 2.5 sample possessed considerably longer fibers as opposed to the LA 2.5 sample and induced a 3-fold greater IL-8 transcriptional response [17]. This hierarchy of potency between the RTI amosite and LA samples observed on an equal mass basis was also consistent with the findings of the animal toxicology studies reported as part of the Libby Action Plan in which rats were dosed by single intratracheal instillation [31]. The concept of particle length as a critical determinant for asbestos toxicity is of course hardly a novel concept as numerous reports have shown correlations between fiber length and carcinogenic outcomes [28,36] as well as on lung injury and inflammation through incomplete phagocytosis of elongated fibers by alveolar macrophages [37].…”
Section: Discussionsupporting
confidence: 68%
“…The current study focused on the IL-8 response in HAEC as a biomarker of inflammation that can be linked with asbestos-induced inflammation observed in parallel animal studies done using these particles [31,38]. Future studies investigating other chemokines and cytokines as well as additional markers of apoptosis, cell survival and DNA damage may shed even more light on the critical determinants that drive different aspects of cellular toxicity in response to asbestos exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure of humans and experimental animals to pulmonary irritants including ozone, particulate matter, cigarette smoke, silica, bleomycin, chlorine or mustard vesicants induces an acute inflammatory response in the lung characterized by multifocal inflammatory lesions, macrophage accumulation, perivascular and peribronchial edema, interstitial thickening, cytotoxicity, bronchiectasis and bronchiolization of alveolar walls which in long term may lead to alterations in lung function, tissue remodeling and pulmonary fibrosis (Churg et al, 2009; Fakhrzadeh et al, 2004; Padilla-Carlin et al, 2011; Pendino et al, 1995; Razavi et al, 2013; Weinberger et al, 2011; Wollin et al, 2014; Yadav et al, 2010). Evidence suggests that macrophage-derived TNFα plays role in these pathogenic responses (Fakhrzadeh et al, 2008; Gossart et al, 1996; Lim et al, 2000; Malaviya et al, 2010; Michael et al, 2013; Weinberger et al, 2011).…”
Section: Role Of Tnfα In Pulmonary Diseasesmentioning
confidence: 99%
“…It is hypothesized that antibodies develop to Jo-1 in tissues such as the lung that are rich in granzyme B cleavage sites and are sensitive to inflammation (Levine et al, 2007). It is therefore possible that the inflammatory environment induced by LA in the lung (Padilla-Carlin et al, 2011) initiates or contributes to a cycle of inflammation, increasing the probability of HisRS cleavage and the production of pathogenic anti-Jo-1 autoantibodies. If further study supports such a cycle following LA exposure and identifies anti-Jo-1 in exposed humans, this ENA may be a valuable marker of pulmonary disease in exposed populations.…”
Section: Discussionmentioning
confidence: 99%